Pengaruh Penggunaan Media Pembelajaran Powtoon Terhadap Motivasi Belajar Ekonomi Siswa Kelas XI di SMA Negeri 2 Percut Sei Tuan T.A 2024/2025 - Lylia Saragi, Sarah; Siar Meiriza, Mica (SJEE (Scientific Journals of Economic Education), 2025)
This study examines the impact of using Powtoon media on the learning motivation of grade XI students at SMA Negeri 2 Percut Sei Tuan. We used a quasi-experimental design with the One Group Pretest-Posttest Design model. Data were collected through learning motivation tests before and after the intervention (pretest and posttest), then analyzed using descriptive and inferential statistics, including t-test and correlation. The results showed a significant increase in students' learning motivation after the implementation of Powtoon media. The average learning motivation score increased from 17.81 (pretest) to 27.08 (posttest), with a significance value of 0.000 (p <0.05). This proves the positive influence of Powtoon on students' learning motivation. Therefore, we recommend the use of Powtoon media in learning to create a more interesting, enjoyable, and student-centered learning atmosphere